Trajetos e representações de docentes da pósgraduação: um olhar a partir dos imaginários e dos dispositivos - Brancher, Vantoir Roberto (2013)
This thesis is in line “Formação, Saberes e Desenvolvimento profissional” from – Programa de PósGraduação em Educação da Universidade Federal de Santa Maria. Thus, the research, that is now explicit, part of the research problem "that representations of professors, in postgraduate, has had professors working in PPG and how these representations has resulted in their professional performance?". To this end, I sought to know the imaginary meanings of a group of professors, working in a PPG in education, about their performance in postgraduate, as well as individual and collective desires of those professors regarding the training of graduates of the same; to identify training places for professors who work in postgraduate; to know the possible devices of professors in postgraduate and eventually characterize the specifics of professors work in postgraduate. To realize these goals, outlined a qualitative study with eight teachers from a Brazilian postgraduate program. After collecting the data, they were analyzed, on hermeneutic perspective from Gadamer (1997). It results in five large blocks of dialogue, namely: representations of teaching performance in postgraduate; individual and collective goals of professors in the program; training places for professors active in PG; teacher training devices in PG, and specificities of teaching in the context of postgraduate studies. With this analytical perspective, I realized that professors working in postgraduate occupy in the collective imagination that context, a place distinct from the other teachers, although, in general, there is no objective convergent regarding the training of graduates course, research, and the overvaluation of the same are among elements that most be those professionals closed. Specifically with regard to teacher training places engaged in postgraduate, I could not establish a social place as the specific context of professor engaged in PG. What I realize is that there seem to be many informal places for training of these professionals, and they still live quite artisan paradigm in training of these professor-researchers. It is important to highlight, the same way that the postgraduate constitutes a space par excellence, equipped with various devices to teacher training, the professionals who work in such a context explicit difficulty finding a time and a space to qualify their professors doings. It is unanimous, among the professors, that competitiveness and individualism lived in the context of PG hinder the joint construction of knowledge. Maybe, it is because of this, that when dropout rates and exchange guidance in PPG are analyzed, they are so significant. Finally, it is relevant to conclude, signaling that, despite the postgraduate constitute primary locus of knowledge building, still lacks systematic studies and programs regarding the monitoring of postgraduate students as well as ex students of the program. Similarly, PG needs research and programs in order to optimize the quality of life of professors and requires continuous training processes established for these professionals.